Recurrent “outsider” intronic variation in the SLC5A6 gene causes severe mixed axonal and demyelinating neuropathy, cyclic vomiting and optic atrophy in 3 families from Maghreb - Mansour-Hendili, Lamisse; Gitiaux, Cyril; Harion, Madeleine; Latouche, Céline; Heron, Bénédicte; Stojkovic, Tanya; Rama, Mélanie; Smol, Thomas; Sophie Jourdain, Anne; Mention, Karine; Nadjar, Yann; Schiff, Manuel; et al. (Frontiers in Genetics, 2024)
Sodium dependent multivitamin transporter (SMVT) deficiency is a very rare autosomal recessive disorder characterized by multisystemic clinical manifestations due to combined biotin, panthotenic acid and lipoic acid deficiency. About 10 families have been described so far.Accurate diagnosis is crucial because of the possibility of a supplementation treatment with proven efficacy. Here we describe 4 new patients (3 additional families) originating from the same world region (Algeria, Maghreb). All patients, born form consanguineous parents, were homozygous carriers of the same intronic variation, outside of canonical sites, in the SLC5A6 gene encoding SMVT.RNA study in one family allowed confirming the pathogenic effect of the variation and re-classifying this variant of uncertain significance as pathogenic, opening the possibility of genetic counseling and treatment. The identification of the same variation in three distinct and apparently unrelated families is suggestive of a founder effect. The phenotype of all patients was very similar, with systematic optic atrophy (initially considered as a very rare sign), severe cyclic vomiting, and rapidly progressive mixed axonal and demyelinating sensory motor neuropathy.